Lost Films: A conversation with Guy Maddin and Evan Johnson on The Forbidden Room - Talbird, John Duncan (Film International, 2015)
Abstract
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9maWluLjEzLjQuMTE2Xzc